Nano-architectured cobalt selenide spheres anchored on graphene oxide sheets for sodium ion battery anode - Ali, Zeeshan; Ali, Muhammad; Mehmood, Ahtisam; Ishfaq, Ayesha; Akram, Muhammad Aftab; Zeb, Akif; Lin, Xiaoming (Frontiers in Materials, 2022)
Aimed at the commercialization of sodium ion batteries (SIBs) technology, researchers have been trying to produce electrode materials with optimally high charge storage capacity, superior rate capability, extended life, and cost-effective components. Herein, we synthesized an electrode of cobalt selenides loaded in carbon spheres and anchored on reduced graphene (CSSs@rGO) for high performance SIBs. This improved structure of CSSs@rGO permits the pseudocapacitive storage of charge and thus enhances the electrical characteristics. It was discovered that the diameter of the carbon sphere had a significant impact on the charge storage capacities of the developed electrode materials, suggesting the probable depth of sodium ion (Na-ion) movement in the electrode materials during charge-discharge. For instance, CSSs@rGO with average diameter of ~70 nm presented best electrochemical performance as anode of SIBs. The nano-architectured CSSs@rGO exhibits excellent ion storage capability with a reversible capacity of 600 mA h g-1 at discharge rate of 100 mA g-1 after 50 cycles While at higher discharge rate, (like 1000 mA g-1) storage capacity as high as 380 mA h g-1 was achieved. In addition to higher charge storage capability and efficient charge storage at higher discharge rates, the developed CSSs@rGO exhibited stable cycling performance for over 3000 cycles, which clearly shows the feasibility of our products. This work will open new approaches for the development of advanced electrode materials of high-performance sodium-ion batteries.